Approval of Raxibacumab for the Treatment of Inhalation Anthrax Under the US Food and Drug Administration “Animal Rule” - Tsai, Chia-Wei; Morris, Stephen (Frontiers in Microbiology, 2015)
On December 14, 2012, the FDA approved raxibacumab, the first product developed under Project BioShield to achieve this milestone, and the first biologic product to be approved through the FDA animal efficacy rule (or “Animal Rule”). Raxibacumab is approved for the treatment of adult and pediatric patients with inhalational anthrax due to Bacillus anthracis in combination with appropriate antibiotic drugs and for prophylaxis of inhalational anthrax when alternative therapies are not available or are not appropriate. The approval of Raxibacumab illustrates many of the challenges that product developers may encounter when pursuing approval under the Animal Rule and highlights a number of important regulatory and policy issues.